Pulmonary benign metastasizing leiomyoma presented as acute respiratory distress. Issue 2 (19th January 2017) - Pastré, Jean; Juvin, Karine; Grand, Bertrand; Gibault, Laure; Valcke, Judith; Israël‐Biet, Dominique
Abstract : Benign metastasizing leiomyoma (BML) is a very rare condition and is characterized by the presence of benign smooth muscle tumours in organs distant from the uterus, most commonly the lung. It generally affects women of reproductive age and prognostic is usually excellent. However, the course of the disease is unpredictable. We report here the case of a 76‐year‐old woman with a previous medical history of uterine benign leiomyomas in whom BML was acutely revealed by a respiratory distress due to voluminous pulmonary and pleural leiomyomas requiring surgical extraction. Clinical evolution was remarkable by resistance to medical treatment and development of rare bone localization. BML is a contradictory entity characterized by benign histological features but with metastatic potential. Pulmonologists as well as oncologists in charge of patients with multiple pulmonary nodules and a history of uterine leiomyoma should be aware of this potential diagnosis in order to implement appropriate diagnostic procedures for this benign tumour. Abstract : We report here the case of a 76‐year‐old woman with a previous medical history of uterine benign leiomyomas in whom benign metastasizing leiomyoma (BML), a very rare condition, was acutely revealed by a respiratory distress due to voluminous pulmonary and pleural leiomyomas requiring surgical extraction. Clinical evaluation was remarkable by resistance to medical treatment and development of rare bone localization.